2020
DOI: 10.1108/ijefm-05-2020-0029
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the drivers of organizational citizenship behaviors (OCB) among corporate meeting attendees

Abstract: PurposeCorporate meetings are a large sector of the global meetings, incentive, convention and exhibition (MICE) industry. However, regular attendance and productive participation by employees are regularly cited as critical problem areas. The purpose of this paper is to investigate how key inhibiting factors related to meeting attendance influence one dimension of employee organizational citizenship behaviors (OCB)–civic loyalty.Design/methodology/approachAn online survey was administered to 229 attendees of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 37 publications
1
14
0
7
Order By: Relevance
“…The study's findings support the notion that festivals need to develop recruitment strategies to hire candidates with transformational leadership qualities due to quality LMX. With high LMX at play, repeat attendance and higher commitment ensue (Yodsuwan et al , 2020), in turn producing lasting and successful events.…”
Section: Discussionmentioning
confidence: 99%
“…The study's findings support the notion that festivals need to develop recruitment strategies to hire candidates with transformational leadership qualities due to quality LMX. With high LMX at play, repeat attendance and higher commitment ensue (Yodsuwan et al , 2020), in turn producing lasting and successful events.…”
Section: Discussionmentioning
confidence: 99%
“…Push factors are the intangible or psychological factors intrinsic to event participants that drive them to decide to attend a MICE event. Related studies have indicated the importance of networking and educational opportunities as push motivational factors (Cassar, Whitfield, Chapman, 2020;Dimitrovski, Seočanac, Luković, 2021;Gračan, Barkiđija Sotošek, Torbarina, 2021;Kim, Kim, Oh, 2020;Kim, Lee, Kim, 2012;Lee, Koo, Chung, 2019;Mair, Thompson, 2009;Pavluković, Cimbaljević, 2020;Severt et al, 2007;Yodsuwan, Pathan, Butcher, 2020;Yoo, Chon, 2008;Yoo, Zhao, 2010). The following sections explain these factors in detail.…”
Section: Push Factorsmentioning
confidence: 95%
“…The majority of previous studies in the MICE context have extensively concentrated on the destination choice from the tourists' and meeting planners' perspectives (Aktas, Demirel, 2019;Crouch, Del Chiappa, Perdue, 2019;Houdement, Santos, Sierra, 2017;Jo et al, 2019;Liang, Latip, 2018;Para, Kachniewska, 2014;Pavluković, Cimbaljević, 2020). Nevertheless, there are few studies that discussed intentions to revisit the destination in the MICE context (Bi, Yin, Chen, 2020;Fitri, 2021;Yodsuwan, Pathan, Butcher, 2020).…”
Section: Revisit Intentionsmentioning
confidence: 99%
See 2 more Smart Citations